Indications and complications of first caesarean section in Tanta University Hospital Versus Sidi Salem Central Hospital a comparative prospective study - El-Bahrawy, Amany Fawzy Abdelaziz; El-Khaiat, Ahmed Mahmoud; Dawoud, Abdelghaffar Saied; El-Kholy, Dina Gamal El-Din (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Caesarean section (CS) is a surgical procedure in which obstetricians do incisions through the mother’s abdomen and uterus to deliver one or more viable babies. The present study was undertaken to determine the indications and complication of first CS. Methods: This prospective comparative study was done in Tanta university hospital and Sidi Salem central hospital, Egypt for one year in the gynecology and obstetrics department. It involved all females delivered by primary CS in the period from November 2020 to November 2021. Data was collected from the admission sheets of the patients and hospital record system. Results: The total number of cases delivered by primary CS was 317, 104 case that represented 14.91%, 11.72% from the total number of cases delivered by CS in Tanta and Sidi Salem hospitals respectively. The most common indication for primary CS in Tanta university hospital among studied group was preeclampsia and eclampsia 53 case (16.71%). While in Sidi Salem central hospital, the most common indication was Failure of labor progress 18 case (17.3%). In Tanta university hospital, the most common complication was post-operative shivering 14 case (19.71%). While in Sidi Salem central hospital, the most common complication was intra operative hemorrhage 17 case (28.33%). Conclusions: The incidence of primary CS in both hospitals was high, so intensive care units, blood banks, incubators with artificial respiration machines and expertise staff must be available at central hospitals in an attempt to decrease the incidence and complications.